White matter hyperintensities and cognition across different Alzheimer's biomarker profiles. Issue 7 (23rd April 2021) - Lam, Sharon; Lipton, Richard B.; Harvey, Danielle J.; Zammit, Andrea R.; Ezzati, Ali; ,
Abstract: Background/Objectives: To examine the association between white matter hyperintensities (WMH) and cognitive domains such as memory and executive function (EF) across different clinical and biomarker categories of Alzheimer's disease (AD). Design: Cross‐sectional study. Setting: Alzheimer's Disease Neuroimaging Initiative. Participants: A total of 216 cognitively normal (CN) participants and 407 participants with mild cognitive impairment (MCI) from the Alzheimer's Disease Neuroimaging Initiative (ADNI) at baseline. Measurements: Based on the 2018 research framework, participants were classified using AT(N) (amyloid‐β deposition [A], pathologic tau [T], and neurodegeneration [(N)]) biomarkers into one of three categories: biomarker negative [A − T− (N)−], amyloid negative but other biomarker positive [A − T ± (N)+ or A – T + (N)±] or amyloid positive [A + T ± (N)±]. Linear regression models were then used to examine the association between WMH and memory composite scores and EF composite scores. Results: Higher WMH burden was associated with worse EF in both CN and MCI subgroups while a significant association between WMH and memory was only found in the MCI subgroup. Furthermore, WMH was associated with EF in the group with A − T ± (N)+ or A – T + (N)± biomarker category, but not for A − T − (N)− (normal biomarker) and A + T ± (N) ± (AD pathology). The association between higher WMH and worse memory was independent of amyloid levels in individuals with MCI with evidence of AD pathology. Conclusion: Vascular disease, as indexed by WMH, independent of AD pathology affects cognitive function in both CN and MCI subgroups. Future studies using the AT(N) research framework should consider white matter lesions as a key biomarker contributing to the clinical presentation of AD.